"In vivo self-assembled" nanoprobes for optimizing autophagy-mediated chemotherapy. (October 2017) - Lin, Yao-Xin; Wang, Yi; Qiao, Sheng-Lin; An, Hong-Wei; Wang, Jie; Ma, Yang; Wang, Lei; Wang, Hao
Abstract: Autophagic therapy is regarded as a promising strategy for disease treatment. Appropriate autophagy regulations in vivo play a crucial role in translating this new concept from benchside to bedside. So far, emerging technologies are required to spatially and quantitatively monitor autophagic process in vivo in order to minimize the cytotoxity concerns associated with autophagy-mediated therapy. We successfully demonstrate the "proof-of-concept" study on autophagy-mediated chemotherapy in mice. Here, we describe a photoacoustic (PA) nanoprobe based on " in vivo self-assembly" idea for real-time and quantitative detection of autophagy in mice for the first time. The purpurin-18 (P18) monomer is connected to hydrophilic poly(amidoamine) dendrimer (4 th generation) through a peptide (GKGSFGFTG) that can be cleaved by an autophagy-specific enzyme, i.e., ATG4B, consequently resulting in aggregation of P18 and enhanced PA signals. Based on this aggregation-induced "turn-on" PA signals, we noninvasively determine the ATG4B activity for monitoring autophagy of tumor in vivo . According to the results of PA imaging, we could optimize chemotherapy efficacy through precisely modulating autophagy, which thereby decrease systemic toxicity from chemotherapeutics and autophagy inhibitors. We envision it will pave the way for developing autophagy-based treatment of diseases in the future.